Crise e estabilização em psicopatologia fundamental - Ávila, Carmen Sílvia (2011)
This dissertation intends to discuss the conceptions of psychic crisis and stabilization, from the analysis of a clinical case in private practicing. Considering the oddity found on this consultation, a reflection concerning some meanings that a crisis may represent have been made, from contributions offered by philosophy, psychiatry and psychoanalysis. Studies concerning hysterical crisis have been retrieved, which were made by Freud when founding the principles of psychoanalysis, concerning the conception of Fundamental Psychopathology and Lacan s Contributions. Regarding the conception offered by Psychiatry, from the clinical case presentation, a reflection about some of the existing treatment methods is made, considering a study concerning Homeostasis and Adjustment, and the importance of particular treatment alternatives, as Therapeutical Communities, for instance